Sintesis Nanopartikel Tembaga Untuk Pelapisan Kain Polipropilena Terhadap Karakterisasi - Musfirah Cahya Fajrah (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
Abstract This journal discusses the distribution of nanoparticles on the surface of the sample cloth and its crystal structure based on XRD results. This study consists of experiments and analysis of results using XRD, SEM, and FTIR. The results of this study concluded that the distribution of nanoparticles was less than optimal, which might be due to not using surfactants to modify the surface of the fabric, making it difficult for the nanoparticle clumps to spread and stick more evenly. Then it can be concluded that the nanoparticles formed are copper oxide (Cu2O) nanoparticles and have a crystal lattice type of a Primitive Cubic or simple cubic crystal lattice type overall, and sizes in the range of 25-130 nm. Keywords: Characterization, Copper Nanoparticles, Polypropylene Fabric